I reperti e i motivi egizi ed egittizzanti a Pompei : indagine preliminare per una loro contestualizzazione - Bellucci, Nikola (Archaeopress Roman archaeology, 2021)
This volume presents a synthesis of research on Egyptian and Egyptianizing material from Pompeii. Starting from the historical context in which to frame these phenomena and proceeding with a review of terminology, the work provides the first up-to-date corpus of Egyptian and Egyptianizing subjects and finds from the famous archaeological site.